Construction of multi-shelled Bi2WO6 hollow microspheres with enhanced visible light photo-catalytic performance. (March 2018) - Qin, Feiyu; Cui, Pengzhen; Hu, Lei; Wang, Zumin; Chen, Jun; Xing, Xianran; Wang, Hao; Yu, Ranbo
Graphical abstract: Highlights: Bi2 WO6 with multi-shelled hollow microstructure was successfully fabricated and the use of ethylene glycol is a key factor. Bi2 O3 /Bi2 WO6 composite with multi-shelled hollow structure were also fabricated when concentration of solution was reduced. Enhanced visible light photocatalytic performance was observed, which are believed due to the unique hollow microstructure. Abstract: As a promising structure in enhancing the photo-catalytic performance of the materials, hollow-shell structure still faces the great challenge of constructing an effective architecture for catalytic application. Herein, multi-shelled hollow microspheres of the visible-light photo-catalyst Bi2 WO6 with shells up to the triple (BWO-MSH), have been synthesized by using a facile and effective carbonaceous template route. Intriguingly, the photo-catalytic reaction rate constant of BWO-MSH sample is nearly 16 times higher than the Bi2 WO6 prepared through solid-state reaction (BWO-SSR). The single-, double-shelled Bi2 WO6 microspheres (Broken) could only be synthesized with lower quality (synthesized with many broken species), and their photo-catalytic performance was nearly the same poor as the BWO-SSR sample. Furthermore, multi-shelled hollow microsphere of Bi2 O3 /Bi2 WO6 (BO/BWO-MSH) composite was also synthesized. The present work not only extends the scope of high-performance complex mixed metal oxides with multi-shelled microstructures, but also brings a good reference to engineer other impressive photo-catalyst.